Enhancing higher order thinking skills among TVET students: HyperDocs as a tool for TVET teachers - Nadzimah Idris,; Mohd Syaubari Othman,; Mohd Muslim bin Md Zalli,; Nurulrabihah Mat Noh, (Penerbit Universiti Kebangsaan Malaysia, 2023)
HyperDocs are interactive digital documents containing links to various digital resources and activities. These learning tools provide students with an interactive and self-directed learning experience that allows them to investigate, generate, and collaborate in a digital environment. HyperDocs have recently experienced a significant surge in usage across various fields. Despite the widespread use of HyperDocs and their potential to improve classroom learning, additional research is required to ascertain their effectiveness in educational settings. This investigation aimed to identify patterns in advanced cognitive abilities to improve Technical and Vocational Education and Training (TVET) educators’ understanding of HyperDocs activities. Using Bloom ’ s Taxonomy as a theoretical framework, the TVET instructor conducted a document analysis of HyperDocs to determine the intellectual level of student activities. During this investigation, a significant quantity of previously unrevealed information has been uncovered. The study results indicate that HyperDocs activities comprise the entire spectrum of cognitive abilities outlined in Bloom’s taxonomy. The analysis reveals that most HyperDocs activities involve lower-order thinking skills such as remembering, comprehending, and applying. Higher-order thinking skills such as analyzing, evaluating, and creating are utilized less frequently, accounting for only 45.1% of all activities. Although HyperDocs’ activities often incorporate primary forms of reasoning, the difference in performance is only 9.8%. The results of the present investigation indicate that the integration of HyperDocs within the Technical and Vocational Education and Training (TVET) domains has the potential to augment cognitive processing.